A historical comparison of U.S. Army & U.S. civilian suicide rates, 1900–2020. (May 2023) - Smith, Jeffrey Allen; Doidge, Michael; Hanoa, Ryan; Frueh, B. Christopher
Highlights: War did not appear to increase suicide rates in U.S. civilians or active-duty army servicemembers. From 1900–2020, U.S. civilian and army servicemember suicide rates appear to fluctuate similarly. Since 1900, U.S. army servicemember and similarly aged civilian male suicide rates have converged. It appears that more universal factors than combat may be similarly affecting both populations. Abstract: Studies examining the perceived association of war time and increasing suicide rates in the U.S. military and U.S. civilian populations have proliferated since the beginning of the Global War on Terror (GWOT). However, additional historical analysis is needed to better place the recent surge in active-duty U.S. Army and U.S. civilian suicide rates into context and better inform researchers, healthcare providers, and policy makers. To do so, a cross sectional study that extracted empirical data from U.S. government websites, publications, and journal articles published from 1900 to 2022 was conducted to identify longitudinal trends. From 1900 to 2020, active-duty U.S. Army soldier and U.S. civilian suicide rates appear to fluctuate similarly, but with soldier rates often displaying more dramatic changes. Since 1900, active-duty U.S. Army soldier and similarly aged U.S. civilian male suicide rates have gradually converged, with the differences in rates narrowing over time. War does not historically appear to increase suicide rates in active-duty U.S. Army soldiers or U.S. civilians. More recently, given the apparent convergence of U.S. Army and similarly aged U.S. civilian male annual suicide rates, larger more universal factors than combat may be similarly affecting both populations.